The speed of trust the one thing that changes everything - Covey, Stephen M. R.; Merrill, Rebecca R. (Free Press, 2006)
This book challenges our age-old assumption that trust is merely a soft, social virtue, and instead demonstrates that it is a hard-edged, economic driver--a learnable and measurable skill that makes organizations more profitable, people more promotable, and relationships more energizing. CEO Covey informs readers how to inspire lasting trust in their personal and professional relationships, and in so doing to create unparalleled success and sustainable prosperity in every dimension of life. He shows business, government, and education leaders how to quickly and permanently gain the trust of their clients, coworkers, partners, and constituents. Like a ripple in the pond, trust begins within each of us personally, continues into our relationships, expands into our organizations, extends into our marketplace relationships, and ultimately encompasses our global society. Covey presents a road map to establish trust on every level, build character and competence, enhance credibility, and create leadership that inspires confidence."--From publisher description